Interdependences with external actors and regime persistence in Eastern Partnership countries*. Issue 1 (2nd January 2021) - Ademmer, Esther; Delcour, Laure; Hoffmann, Katharina; Jaroszewicz, Marta
ABSTRACT: This article addresses how both external democratic and non-democratic actors impact the persistence of non-democratic regimes in third countries. We focus on asymmetrical interdependences and advance the literature on the role of transnational flows by highlighting under which conditions and based on which mechanisms interdependences contribute to the persistence of non-democratic regimes. We investigate if the dominant mechanisms emerging from interdependences vary with the type of interdependence (vulnerability or sensitivity). We draw on evidence from empirical studies of Armenia, Belarus and Azerbaijan and their interdependences with Russia and the EU in the period of 2005–2015.